Schizophrenia and deliberate self-harm: a systematic review of risk factors. - Haw, C; Hawton, K; Sutton, L; Sinclair, J; Deeks, J (2005)
Deliberate self-harm (DSH) is a strong predictor of suicide in schizophrenia. The aim of this review was to identify risk factors for DSH in schizophrenia. This systematic review of the international literature examined cohort and case-control studies of patients with schizophrenia or related diagnoses that reported DSH as an outcome. Studies were identified by searching electronic databases and reference lists, and by consulting international experts. Fourteen studies met the eligibility criteria. Of the 29 variables examined by two or more studies, five (past or recent suicidal ideation, previous DSH, past depressive episode, drug abuse or dependence, and higher mean number of psychiatric admissions) were associated with an increased risk of DSH, and one (unemployment) was associated with a reduced risk. Schizophrenic patients with these risk factors need careful follow-up and monitoring, with treatment of any associated comorbid depression or drug abuse. Large, prospective studies of DSH in schizophrenia are needed to further define risk factors and to build on the findings of this review.